Analyzing the relationships between learners' motivation and observable engaged behaviors in a gamified learning environment. Issue 154 (October 2021) - Lavoué, Élise; Ju, Qinjie; Hallifax, Stuart; Serna, Audrey
Highlights: We conducted an ecological study with 257 students from 5 middle schools We provide a model of engaged behaviors with a gamified interactive environment Learners' behaviors depend on their initial motivation and player profile Different types of behavior are linked to different variations in learner motivation We provide recommendations for the design of motivational affordances Abstract: Over the last ten years, gamification has been widely integrated in digital learning environments as a way to increase learners' motivation. However, little is known about engaged behaviors adopted by learners when using gamified learning environments. In this paper, we analyze learners' interactions with a gamified learning environment to study learners' engagement in this particular context and to identify the factors that influence engaged behaviors. We also analyze the complex relationships that exist between learners' engagement and motivation. We conducted a large-scale field study in ecological conditions, involving 257 students (13-14 years' old) in 12 classes, from 4 different middle schools. We identified a model of engagement that distinguishes two types of engaged behaviors: an achievement-oriented engagement for initially intrinsically motivated learners or high achiever learners, and a perfection-oriented engagement for low achiever learners. We show that each type of engaged behavior has a specific impact on the variation in learners' motivation during the learning activity. This model contributes to a better understanding of how gamification can affect learners' engaged behaviors and motivation during the learning activity according to their initial motivation and player profile. These findings open up new perspectives in terms of motivational affordances, as well as the design and dynamic adaptation of gamification based on learners' interaction traces with the learning environment.